On two conceptions of formality in 19th century symbolic logic - Legris, Javier (2010)
This paper deals with two conceptions of formality underlying 19th Century symbolic logic. In both conceptions the idea of symbolic system played an important role. The discussion is guided by a distinction devised by Gottlob Frege between two sorts of formal theories. In the paper both conceptions are connected to the attempts of constructing universal scientific languages at that time. As a conclusion it will be shown that each of the two conceptions of formality places logic in different levels and determines different conceptions of universality.